2018
DOI: 10.1101/368274
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Apparent thinning of visual cortex during childhood is associated with myelination, not pruning

Abstract: Microstructural mechanisms underlying apparent cortical thinning during childhood development are unknown. Using functional, quantitative, and diffusion magnetic resonance imaging in children and adults, we tested if tissue growth (lower T 1 relaxation time and mean diffusivity (MD)) or pruning (higher T 1 and MD) underlies cortical thinning in ventral temporal cortex (VTC). After age 5, T 1 and MD decreased in mid and deep cortex of functionally--defined regions in lateral VTC, and in their adjacent white mat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…The differential rate of thinning is greatest in association cortex (component 1) compared to primary motor and sensory regions (components 2 and 5), with the exception of the visual cortex (component 4). We anticipate these differences in regional rate of change reflects the differential progress of microstructural processes including synaptic pruning (Huttenlocher, 1979), although recent evidence has suggested that apparent cortical thinning in the visual cortex may be dependent on tissue contrast changes due to intracortial myelination, rather than synaptic remodelling (Natu et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…The differential rate of thinning is greatest in association cortex (component 1) compared to primary motor and sensory regions (components 2 and 5), with the exception of the visual cortex (component 4). We anticipate these differences in regional rate of change reflects the differential progress of microstructural processes including synaptic pruning (Huttenlocher, 1979), although recent evidence has suggested that apparent cortical thinning in the visual cortex may be dependent on tissue contrast changes due to intracortial myelination, rather than synaptic remodelling (Natu et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…While it represents a robust and stable measure, the interregional thinning profile is unable to provide information neither at an individual level nor across time; hence, a portion of the variability remains unexplored. Relative disparity amongst studies might reside on different characterizations of cortical thinning variability 27 11,26,27,52 . Lack of findings may relate to the nature of the interregional profiles, which represent snapshots in time and, hence, are determined by the differential sum of processes that modulate cortical thickness in each area.…”
Section: Technical Considerationsmentioning
confidence: 99%
“…The human cerebral cortex consists on several types of cells, which can be classified into neuronalmostly pyramidal cells and interneurons -and non-neuronal cells -mostly glial cells, namely microglia, astrocytes and oligodendrocytes [22][23][24] . Histological data suggest that regional variations of cortical thickness may be associated with the number of non-neuronal cells and neuropil volume 25,26 . Yet, this ex vivo approach may be less suited to uncover the microstructural substrate driving age-related changes in cortical thickness in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…28,48 This indeterminacy highlights how a number of possibly divergent, heterochronic neurobiological mechanisms may give rise to similar observed patterns of cortical morphology, as highlighted by recent reports of the dependence of MRI-based cortical thickness estimates on intracortical myelin content during development. 53,54 By comparing genes with high expression in regions of accelerated thinning with large databases of gene-disease associations, we found significant enrichment of several cognitive disorder terms. DisGeNET is a discovery platform containing gene-disease associations compiled from multiple sources including GWAS data, animal models and literature searches.…”
Section: Discussionmentioning
confidence: 96%